Biomarker modelling of Alzheimer's disease using in vivo Braak staging. (20th December 2022) - Therriault, Joseph; Pascoal, Tharick A; Lussier, Firoza Z; Tissot, Cécile; Bezgin, Gleb; Servaes, Stijn; Benedet, Andréa Lessa; Ashton, Nicholas J.; Karikari, Thomas K; Rodriguez, Juan Lantero; Wang, Yi‐Ting; Arias, Jaime Fernandez; et al.
Abstract: Background: Gold standard diagnostic methods for AD rely on staging systems to measure disease severity, which have not yet been incorporated into the in vivo biological research framework for AD. The topographical information conferred by tau‐PET offers the potential to translate the gold standard histopathological Braak staging system to living individuals. Method: Using the topographical information from [ 18 F]MK6240 tau‐PET, we applied the Braak tau staging system to 324 living individuals. We used PET‐based Braak stage to model the trajectories of amyloid‐b, phosphorylated tau in cerebrospinal fluid (pTau181, pTau217, pTau231, pTau235 ) and plasma (pTau181, pTau231 ), neurodegeneration and cognitive symptoms. Result: PET‐based Braak stages were We identified nonlinear AD biomarker trajectories corresponding to the spatial extent of tau‐PET, with modest biomarker changes detectable by Braak stage II and significant changes occurring at stages III‐IV, followed by plateaus. Early Braak stages were associated with isolated memory impairment, while Braak stages V‐VI were incompatible with normal cognition. Follow up tau‐PET scans indicated sequential progression of in vivo Braak stages over time, with progression beyond Braak stage III requiring the presence of amyloid‐beta abnormality. Conclusion: Our results support PET‐based Braak staging as a framework to model the natural history of AD, as well as monitor AD severity from presymptomatic to clinical dementia phases.